PROBIOTICS BACTERIA AS QUORUM SENSING DEGRADER CONTROL Aeromonas hydrophila PATHOGENICITY IN CULTURED RED HYBRID TILAPIA - Omar, Noor Syazwani; Emilia, Sharifah Noor; Danish-Daniel, Muhd; Iehata, Shumpei; Mohd Ikhsan, Natrah Fatin (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2023)
Quorum sensing (QS) is the interaction of bacteria cell-to-cell to regulate various bacterial functions, including bacterial virulence. It has been suggested that QS interruption is an anti-infective strategy to combat diseases in aquaculture. This research was conducted to isolate the potential probiotics bacteria as QS degrader from the fish gut and investigate its efficiency in reducing Aeromonas hydrophila pathogenicity by in vitro and in vivo assay. In this study, three isolates from the fish gut were able to degrade N-acyl homoserine lactone (AHL), one of the QS signals of A. hydrophila. Based on 16S rDNA sequence analysis, isolate CPi12 was identified as Klebsiella sp., CBa5 and CBa7 were identified as Enterobacter tabaci. These isolates were co-cultured with A.hydrophila for five days. Results revealed that all isolates could decrease the AHL production of A. hydrophila but did not affect the growth of the pathogen. In vivo assay results showed that isolate CPi12 reduced the pathogenicity of A.hydrophila against tilapia with a significantly higher survival rate (p<0.05) of fish in the CPi12-fed group than the control group. Meanwhile, isolate CBa7 was significant (p<0.05) for growth performance, including specific growth rate (SGR), weight gain (WG), feed conversion ratio (FCR), mean weight gain (MWG), and average daily growth (ADG) among whole treatment and control group. These results displayed that the probiotics bacteria as QS degrader isolated from the fish gut could control the pathogenicity of Aeromonas hydrophila. It has been proposed that QS degrader bacteria might be an alternative solution for disease control.